Beta-phosphate tricalcium colloidal processing. Issue 3 (15th February 2020) - Porsani, N.K.; Santos, M.K.; Rocha, A.M.; Trombini, V.; Ana, P.A.; Tercini, M.B.; Setz, L.F.G.
Abstract: Beta Tricalcium phosphate (β-TCP) is an important ceramic material for biomedical applications and can help the regeneration of bone. In this work, it was studied the rheological behaviour of β-TCP suspensions, using the slip casting forming method, in order to adjust the necessary conditions for future use as bone graft. The characterization of the material powder was performed by the analysis of the specific surface area, the particle shape, the morphological aspect, the particle size distribution and the Zeta potential in water media. The suspensions studied were produced with distilled water, using sodium silicate as dispersant, and homogenized in ball mill for times up to 24 h. The rheological measurements were performed using a rotational rheometer. Products generated with 2.0 wt% of sodium silicate, with the addition of 0.5 wt% carboxymethyl cellulose and homogenized in ball mill during 24 h after sintering had porosity that can be adequate for a future use as biomaterial.